The Bariatric Pyramid: A framework for therapeutic targets - Sanjay Kalra; Nitin Kapoor; Manash P Baruah; Saurabh Arora; Ashok Kumar Das (Journal of the Pakistan Medical Association, 2023)
The Bariatric Pyramid is a model which serves to explain the goals of obesity management, act as a milestone for monitoring of therapy, and to benchmark the utility of various anti-obesity medications and interventions. Built upon a base of sustainability, it lists three more desired aspects of care: sufficiency (sufficient strength) safety and security. Each of the four aspects of the pyramid: sustainability, sufficiency safety and security have three angles, which allows the reader to understand them easily. The model that we propose is useful in training health care professionals, in therapeutic patient education, for assessing various anti-obesity therapies, and in reaching the right decision while managing obesity. Keywords: Anti-obesity medication, clinical decision aid, obesity, overweight, therapeutic patient education, person centered care.